Carboxymethylcellulose-coated magnesium-layered hydroxide nanocomposite for controlled release of 3-(4-methoxyphenyl)propionic acid - Norhayati Hashim (Tanjong Malim, 2020)
Carboxymethylcellulose-coated magnesium-layered hydroxide nanocomposite for controlled release of 3-(4-methoxyphenyl)propionic acid by Norhayati Hashim